Pengaruh Tingkat Perputaran Kas, LDR dan Efektivitas Badan Pengawas Terhadap Rentabilitas Ekonomis LPD Kota Denpasar - Budastra, Kadek Odika Meiva; Wirasedana, I Wayan Pradnyantha (E-Jurnal Akuntansi; Vol 22 No 2 (2018)DO - 10.24843/EJA.2018.v22.i02.p03, 2018)
LPD aims to assist villagers in the fertilization of capital to be developed in order to improve people's economic business. The efficiency of an LPD can be assessed from the profitability. This study aims to determine the effect of cash turnover rate, loan to deposit ratio, and the effectiveness of regulatory bodies on economic rentability at LPD in Depasar period 2014-2016. This study uses purposive sampling method. The data analysis technique used in this research is multiple linear regression with first classical assumption test ie normality test, autocorrelation test, multicolinieratias test, and heteroscedasticity test. The result of the conclusion of this research is that the variable of cash rotation has an insignificant effect on economic profitability, the variable of loan to deposit ratio has significant positive effect on economic profitability, and the effectiveness of regulator has a significant positive effect on economic rentability of LPD in Denpasar period 2014 -2016. Keywords: Cash turnover, ldr, effectiveness of the regulatory body, economic profitability